2018
DOI: 10.3390/nu10070931
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Pepino (Solanum muriactum Ait) Leaves Ameliorate Lipid Accumulation and Oxidative Stress in Alcoholic Fatty Liver Disease

Abstract: Chronic alcohol intake leads to alcoholic fatty liver. The pathogenesis of alcoholic fatty liver is related to abnormal lipid accumulation, oxidative stress, endotoxins, and cytokines. Solanum muricatum Ait. (Pepino) is a plant food commonly cultivated in the Penghu island, Taiwan. Previous studies indicated that the aqueous extract of pepino was able to attenuate diabetic progression via its antioxidative and anti-inflammatory effects. However, the mechanisms of the antioxidative and anti-inflammatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
1
26
1
1
Order By: Relevance
“…Though a decrease in weight gain was not observed for the groups receiving alcoholic beverages in our study, some studies have reported this to be caused by prolonged alcohol intake [24,25,26], including the murine studies [27]. Milat et al [28] reported similar observations in a rat model, wherein one-month and three-month-old male rats received white wine (13% ethanol) for four weeks and a significantly lower body mass was recorded in comparison with their control group.…”
Section: Discussioncontrasting
confidence: 66%
“…Though a decrease in weight gain was not observed for the groups receiving alcoholic beverages in our study, some studies have reported this to be caused by prolonged alcohol intake [24,25,26], including the murine studies [27]. Milat et al [28] reported similar observations in a rat model, wherein one-month and three-month-old male rats received white wine (13% ethanol) for four weeks and a significantly lower body mass was recorded in comparison with their control group.…”
Section: Discussioncontrasting
confidence: 66%
“…Acetyl coenzyme A carboxylase (ACC) is a rate-limiting enzyme that catalyzes the first step of fatty acid synthesis and metabolism and plays an important role in the lipid metabolism. ACC1 is mainly expressed in liver and catalyzes the synthesis of long-chain fatty acids, thereby promoting the progression of hepatic steatosis [60,61,62]. In our study, POE prevented the ethanol-induced liver injury by decreasing the expression of miR-122, ACC1 mRNA and protein, and increasing the expression of LPL-mRNA and protein in rats.…”
Section: Discussionsupporting
confidence: 57%
“…Diterpenoid alkaloids and 6-methoxynaringenin in the Scutellaria barbata extracts had the strongest effect on downregulating the secretion of NO, PE2, IL-6, IL-1 β induced by LPS and P-JNK signaling pathway activation [4244]. Moreover, the water extracts of Bittersweet herb and Herba artemisiae scopariae can alleviate inflammation by inhibition of NF- κ B pathway that reduces the generation of proinflammatory cytokines like IL-1 β and IL-6 [4547]. Other components in YAXJ such as Astragalus membranaceus have the effects of invigorating Qi, generating Yang, strengthening exterior, and stopping sweating, often used for the rehabilitation of patients with weak constitution.…”
Section: Discussionmentioning
confidence: 99%